1998
DOI: 10.30843/nzpp.1998.51.11675
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase and glutathione S-transferase in the earthworm <i>Apporectodea caliginosa</i> as biomarkers of organophosphate exposure

Abstract: Two potential biomarkers of pesticide contamination were investigated in Apporectodea caliginosa. Juvenile earthworms were exposed to sub-lethal concentrations of the organophosphates chlorpyrifos and diazinon to assess their effect on cholinesterase and glutathione S-trasferase activities. Cholinesterase which is inhibited by organophosphates, was inhibited by 72% by diazinon (P<0.001) and 87% by chlorpyrifos (P<0.001) within 1 day of exposure and remained depressed 14 days after exposure. Glutathione S-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
1
7
1
Order By: Relevance
“…Similar results have been reported in A. caliginosa earthworms exposed to chlorpyrifos at 0.51 and 10 mg/kg for 21 days with 84% and 97% AchE inhibition respectively (Sanchez-Hernandez et al, 2014). Booth et al (1998) reported AChE inhibition of up to 87% by chlorpyrifos even on day 1 of exposure, and remained low for 14 days. In our study, relative AChE activity (V max , indicative of total enzyme activity) in earthworms exposed for 7 and 14 days decreased significantly in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar results have been reported in A. caliginosa earthworms exposed to chlorpyrifos at 0.51 and 10 mg/kg for 21 days with 84% and 97% AchE inhibition respectively (Sanchez-Hernandez et al, 2014). Booth et al (1998) reported AChE inhibition of up to 87% by chlorpyrifos even on day 1 of exposure, and remained low for 14 days. In our study, relative AChE activity (V max , indicative of total enzyme activity) in earthworms exposed for 7 and 14 days decreased significantly in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results have been reported in A. caliginosa earthworms exposed to chlorpyrifos at 0.51 and 10 mg/kg for 21 days with 84% and 97% AchE inhibition respectively (Sanchez‐Hernandez et al, ). Booth et al () reported AChE inhibition of up to 87% by chlorpyrifos even on day 1 of exposure, and remained low for 14 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Templeton silt loam (17% clay, 52% silt, 31% sand, 3.9% organic matter) was used for these experiments. Juvenile earthworms 3 months old and weighing between 200 and 300 mg were exposed for 28 days to the highest sub-lethal concentration (high concentration) of chlorpyrifos (28 mg/kg) or diazinon (60 mg/kg), as determined in previous experiments (Booth et al 1998), and a laboratory-simulated field rate (low concentration) for each pesticide and compared with controls. The laboratorysimulated field rates were determined as an estimate of the amount of pesticide that earthworms are exposed to in the soil.…”
Section: Assessment Of Earthworm Fecunditymentioning
confidence: 99%
“…This study is part of a multistage project to develop a suite of validated biomarkers for exposure to the organophosphates, diazinon and chlorpyrifos, that can be related to higher-order effects. Stage one of this research was evaluation of potential biomarkers in the earthworm species Aporrectodea caliginosa (Savigny) under laboratory conditions (Booth et al 1998). Stage two was evaluation of these biomarkers in a semi-field and field experiment (Booth et al 2000).…”
Section: Introductionmentioning
confidence: 99%